Needs Analysis of E-Student English Worksheets with Islamic Values Integration at Islamic Senior High School - Armelia Husna; Yuli Tiarina (Universitas Negeri Padang, 2023)
E-student English worksheets with Islamic values integration give many advantages to the students and teachers in Islamic senior high school. However, based on the observation, there is no E-student English worksheet with Islamic values integration. Therefore, to know the needs of students on E-student English worksheets with Islamic values integration, it is important to do a study about needs analysis of E-student English worksheets with Islamic values integration. This study aims to find out what are the needs of E-student English worksheets with Islamic values integration at MAN 1 AGAM. This research was quantitative descriptive with the data collection technique using an online close-ended questionnaire. The respondents in this study were 75 students of XI MAN I AGAM. They were given 24 close-ended questions. The result showed that all the aspect of students’ need on E-student English worksheets with Islamic values integration shows 88% in the criteria ‘most need’. Thus, almost all the students need E-student English worksheets with Islamic values integration at MAN 1 AGAM. In addition, further research related to E-student English worksheets with Islamic values integration is suggested to do